2015
DOI: 10.1007/s10973-015-4869-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel organic antibacterial thermal stabilizers for transparent poly(vinyl chloride)

Abstract: A novel kind of antibacterial thermal stabilizers for transparent poly(vinyl chloride), bis-uracil compounds with different alkyl chain length, was synthesized by the condensation of 6-amino-1,3-dimethyluracil with aliphatic aldehydes and characterized with 1 H NMR spectra. Not only high stabilization efficiency which increased with the increasing of alkyl chain length was obtained to prevent PVC from degradation, special antibacterial properties could also be acquired in the mean time of keeping PVC highly tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 35 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…The mechanism of LaSD as a thermal stabilizer in PVC was studied through the following two experiments [21,22].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of LaSD as a thermal stabilizer in PVC was studied through the following two experiments [21,22].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, a large number of studies have shown that the presence of uracil in compounds has a positive effect on improving the thermal stability of PVC [19,20,21,22]. Sabaa et al investigated uracil derivatives as PVC thermal stabilizers through a series of experiments and found that they can significantly improve the thermal stability of PVC [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research of zinc complexes 16,17 and organic thermal stabilizers [18][19][20] reported by our group showed that the carboxylate groups not only attract the zinc ion but also can replace the unstable chlorine atom on PVC chains, which inhibits the zipper-like dehydrochlorination of PVC. Additionally, an electron shift can be produced on the connected amino group in the double-ring structure of zinc norfloxacin, which leads to the strong absorption of HCl and the delay of the autocatalytic effect, that the released HCl accelerates the removal of other HCl molecules from PVC chains.…”
Section: Introductionmentioning
confidence: 99%
“…Because the time of fabrication of PVC is relatively short, and determination of the amount of stabilizer consumed after various processing times indicates that most of the stabilizer remains unreacted, the final product contains M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 large amount of heat stabilizer. For this, recently, a class of organic thermal stabilizers possessing antimicrobial activity has been developed to obtain thermally stable antimicrobial PVC composites to be utilized in various biomedical applications [10][11][12].…”
Section: Introductionmentioning
confidence: 99%